Editorial (v.14, n.1, jan./jun. 2018) - Education and management of newspapers: new paths and perspectives in science - Cruz, José Anderson Santos (Temas em Educação e Saúde, 2018)
Scientific communication, today, has undergone several changes. Among them, we highlight the new editorial policies for periodicals, with the purpose of obtaining more international visibility. For this, it is necessary the inclusion of journals in index bases, directories, libraries and other ways of preserving the metadata of articles. To index, qualify and obtain more visibility in the journals, the requirements for publication are increasing; regarding the qualification of the articles, for the submission of the manuscripts to qualified journals, or for those who wish to qualify in a scenario of scientific competitiveness.